2020
DOI: 10.1055/s-0040-1701220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Combined ACL and Anterolateral Ligament Reconstruction: A Narrative Review from the SANTI Study Group

Abstract: Lateral extraarticular procedures (LEAPs) in the anterior cruciate ligament (ACL)-injured knee were widely abandoned in the 1990s but have seen a recent resurgence. The aim of this review was to demonstrate that anterolateral ligament reconstruction (ALLR) is associated with evidence of significant advantages and no evidence of historical concerns. A narrative review of the literature was performed. Combined ACL + ALLR is associated with improved outcomes when compared against isolated ACL reconstruction, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 47 publications
(70 reference statements)
2
47
0
5
Order By: Relevance
“…Currently, indications for combined ALL and ACL reconstruction in primary cases consist of patients who practice high-demand sports activities associated with frequent rotational knee movements, young patients, ligamentous hyperlaxity/genu recurvatum, or cases of chronic injury. 10,17,31,33 The findings of the present study indicate that an observed ALL injury on MRI examination is a factor related to a higher incidence of reconstruction failure and possible worse clinical outcomes. ALL reconstruction has been shown to be effective in decreasing the number of reinjuries in other scenarios, and we believe that its application should be considered in patients with this finding on imaging.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Currently, indications for combined ALL and ACL reconstruction in primary cases consist of patients who practice high-demand sports activities associated with frequent rotational knee movements, young patients, ligamentous hyperlaxity/genu recurvatum, or cases of chronic injury. 10,17,31,33 The findings of the present study indicate that an observed ALL injury on MRI examination is a factor related to a higher incidence of reconstruction failure and possible worse clinical outcomes. ALL reconstruction has been shown to be effective in decreasing the number of reinjuries in other scenarios, and we believe that its application should be considered in patients with this finding on imaging.…”
Section: Discussionmentioning
confidence: 58%
“…This nonhealing scenario is important because biomechanical studies have suggested that in cases of an acute combined injury of the ACL and the anterolateral structures, isolated reconstruction of the ACL does not reestablish normal knee biomechanics. 20,29 Although numerous clinical studies have proven significant advantages of ALL reconstruction, 31 the influence of an associated ALL injury on postoperative outcomes of patients undergoing isolated ACL reconstruction has not been well-studied. In addition, research on the prognostic value of an ALL injury is limited to case series with a short follow-up and for chronic injuries to the ACL.…”
Section: Evaluated This Parameter Andmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The purpose of the meta-analysis is to provide highlevel evidence for clinical practice. Although several well-performed level III studies [10][11][12] included in the narrative review from the SANTI group 13 support the advantage of ALLR regarding reduced ACL graft rupture rates, the nonrandomization and retrospective study design prevented the studies from inclusion in our meta-analysis. Whether the risk of bias from the inclusion of comparable studies with lower-level evidence is outweighed by the benefits requires further investigation.…”
mentioning
confidence: 99%
“…numerous clinical studies demonstrating a reduction in ACL graft rupture rates with an EAT [17][18][19][20] ; all clinical series of combined anterior cruciate ligament reconstruction (ACLR) þ EAT since 2015 have reported good clinical outcomes in adults [21][22][23][24][25][26][27][28][29][30][31][32] and skeletally immature patients 33,34 ; numerous clinical studies demonstrating a high proportion (up to 90% in acute ACL-injured knees) of injuries to anterolateral structures, both on imaging and at open lateral exploration [35][36][37][38] ; and finally the fact that the theoretical early degenerative change has never been clinically demonstrated. 39 So, as Rossi said in his brilliant editorial commentary, "Anterolateral Ligament Augmentation for the Anterior Cruciate Ligament-Deficient Knee DebatedThe Proof Is in the Pudding," 40 "The story is not anymore "if" augmentation should be considered but "when" and, maybe more important, "how" to augment.…”
mentioning
confidence: 99%